Effect of Impression Technique on Denture Retention and Patient Satisfaction: A Comparative Clinical Study - Robina Tasleem, Fahimullah, Sajjad Hussain, Shoaib Rahim, Sadia Akram, Hoda Lotfy Abouzeid, Asim Elsir Elmahdi, Ashfaq Yaqoob, Razan Saeed Alshahrani (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To compare satisfaction levels of patients wearing maxillary completes denture fabricated by closed mouth and an open mouth impression techniques. Methods: This Comparative clinical study was conducted at the Department of Prosthodontics, Armed Forces Institute of Dentistry (AFID), Rawalpindi. Eighty-four edentulous patients were included in this study; the patients were randomly allocated into two groups. Group A patients were provided with dentures fabricated by closed mouth impression technique and Group B patients were provided with dentures fabricated by open mouth impression technique. The patient’s satisfaction level was assessed after six weeks of denture insertion with a questionnaire attached as Annex-A. Results: Out of 42 patients in group A, 12 were highly satisfied, 28 moderately satisfied and 2 poorly satisfied. In group B patients, 9 were highly satisfied, 25 moderately satisfied and 8 poorly satisfied. Retention was highest (81.0%) in patients of group A compared to group B (19%). Moderately satisfied patients were more significantly (p=0.04) more (69.0% in group A and 71.4% in group B) comfortable compared to highly satisfied (26.2% in group A and 19.0% in group B) and poorly satisfied (4.8% in group A and 19.5% in group B) in both groups. There was no statistically significant difference among patients in both groups when their satisfaction with their ability to chew with dentures was compared. Regarding satisfaction with speech ability more patients were moderately satisfied (28.6% in group A) compared to the number of patients (21.4%) in group B. Overall, 70.2% of moderately satisfied category showed significantly higher frequency of patients followed by 17.9% patients each lying in highly satisfied and poorly satisfied patients, categories. Clinical implication: Final impression in complete denture (CD) fabrication is very crucial step that can affect overall prognosis of CD treatment and therefore, patient satisfaction with CDs. A simplified closed mouth impression approach to complete denture treatment, omitting the border molding and definitive impression appointment, has been suggested as an alternative to the conventional open mouth approach. Conclusion: Dentures fabricated by closed mouth impression technique are more stable and functionally better compared to those constructed by open mouth impression technique. Keywords: Final impression technique, complete dentures, Retention, Comfort, Speech ability, Patient Satisfaction